Proceedings of the Fourth International Conference on Signal and Image Processing 2012 (ICSIP 2012) Volume 1 - S, Mohan; Kumar, S Suresh; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
The proceedings includes cutting-edge research articles from the Fourth International Conference on Signal and Image Processing (ICSIP), which is organised by Dr. N.G.P. Institute of Technology, Kalapatti, Coimbatore. The Conference provides academia and industry to discuss and present the latest technological advances and research results in the fields of theoretical, experimental, and application of signal, image and video processing. The book provides latest and most informative content from engineers and scientists in signal, image and video processing from around the world, which will benefit the future research community to work in a more cohesive and collaborative way.
Preface -- Table of Contents -- About the Editors -- About ICSIP 2012: Conference Details, Organizing Committee -- Papers -- Author Index.
Keywords: Engineering; Text processing (Computer science; Computer vision; Engineering; Signal, Image and Speech Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Document Preparation and Text Processing